2001
DOI: 10.1023/a:1010667524422
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The Late Maunder Minimum (LMM, 1675(LMM, -1715 denotes the climax of the 'Little Ice Age' in Europe with marked climate variability. Investigations into interannual and interdecadal differences of atmospheric circulation between the LMM and the period 1961-1990 have been performed and undertaken based upon sea level pressure (SLP) difference maps, empirical orthogonal function (EOF) analysis, and objective classification techniques. Since the SLP during the LMM winter was significantly higher in northeastern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 203 publications
(39 citation statements)
references
References 71 publications
1
34
1
3
Order By: Relevance
“…This is consistent with the circulation perturbation in Fig. 6 and has also been deduced from indirect proxies (Luterbacher et al 2001), including the spatial patterns of changes in recorded harvest dates (Wanner et al 1995). This strongly suggests a link with the incidence of long-lived winter ''blocking'' events in the eastern Atlantic at low solar activity.…”
Section: Regional Climate Effectssupporting
confidence: 88%
“…This is consistent with the circulation perturbation in Fig. 6 and has also been deduced from indirect proxies (Luterbacher et al 2001), including the spatial patterns of changes in recorded harvest dates (Wanner et al 1995). This strongly suggests a link with the incidence of long-lived winter ''blocking'' events in the eastern Atlantic at low solar activity.…”
Section: Regional Climate Effectssupporting
confidence: 88%
“…Other studies found a negative correlation between the same parameters, however (Kirov and Georgieva, 2002). Studies on Maunder Minimum have indicated a direct relationship between the low solar activity during this period and the negative NAO phase (Wanner et al, 2008;Slonosky et al, 2001;Luterbacher et al, 2001;Xoplaki et al, 2001;Shindell et al, 2001;Langematz et al, van Loon and Meehl (2008) in a study applying the composite mean difference method. These results were confirmed by Roy and Haigh (2010) by means of multiple linear regression applied to time series of 155 years.…”
Section: Introductionmentioning
confidence: 79%
“…But in eastern Europe, western Russia and parts of eastern Scandinavia, summer temperatures were normal or slightly warmer than average. Temperature fluctuations in the central and eastern Mediterranean are less certain, owing to a lack of temperature station data for these areas 6,7 .…”
Section: Summer 1816 After Tamboramentioning
confidence: 99%